Gallbladder wall thickening as a sign of esophageal varices in chronic liver disease* - , Galip ERSÖZ, Ömer ÖZÜTEMİZ, Ulus Salih AKARCA, Mustafa YILMAZ, Zeki KARASU, Yücel BATUR (Turkish Journal of Gastroenterology 1, 2019)
-